2018
DOI: 10.1371/journal.pone.0193874
|View full text |Cite
|
Sign up to set email alerts
|

Physical modeling of vortical cross-step flow in the American paddlefish, Polyodon spathula

Abstract: Vortical cross-step filtration in suspension-feeding fish has been reported recently as a novel mechanism, distinct from other biological and industrial filtration processes. Although crossflow passing over backward-facing steps generates vortices that can suspend, concentrate, and transport particles, the morphological factors affecting this vortical flow have not been identified previously. In our 3D-printed models of the oral cavity for ram suspension-feeding fish, the angle of the backward-facing step with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(52 citation statements)
references
References 66 publications
3
44
0
Order By: Relevance
“…The 100µm mesh only had 44% open area, less than the 55% open area for the 140µm mesh, which contributed to the disparity. The higher fluid exit ratio in the Sanderson filter was correlated with the formation of larger sustained vortices, as predicted by Brooks et al (2018). Marshall filter was modified to improve its fluid exit ratio by extending the filter frame and adding additional slots (nine instead of five).…”
Section: Baseline: Pre-collaboration Filtersmentioning
confidence: 77%
See 2 more Smart Citations
“…The 100µm mesh only had 44% open area, less than the 55% open area for the 140µm mesh, which contributed to the disparity. The higher fluid exit ratio in the Sanderson filter was correlated with the formation of larger sustained vortices, as predicted by Brooks et al (2018). Marshall filter was modified to improve its fluid exit ratio by extending the filter frame and adding additional slots (nine instead of five).…”
Section: Baseline: Pre-collaboration Filtersmentioning
confidence: 77%
“…Fouling of the filter with particles or solutes is a major limitation of many industrial filtration processes (Imbrogno and Belfort 2016;Jaffrin 2012). Previous research by one of the authors introduced a new filtering mechanism called vortical cross-step filtration based on physical models of ram filter-feeding fish (Brooks et al 2018;Sanderson et al 2016). The basic cross-step filter design published by Sanderson et al (2016) has been proposed for the adsorption of biological macromolecules (Zhou et al 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We suspect that at slower speeds (0.25 BL s −1 ), the change in depth from the first region of the model to the second region does not create a strong enough pressure change to induce strong vortical flow. Brooks et al (2018) recently showed that pressure drops created across the filtering apparatus in suspension-feeding fishes are crucial to the development of vortical structures. As a result of the decrease in pressure, vortices that develop across region 2 are slow moving and do not accelerate across the model.…”
Section: Discussionmentioning
confidence: 99%
“…Forced vortices occur at low to moderate Reynolds numbers and require a continuous external source of kinetic energy to continue moving (Brooks et al, 2018), such as would be provided by buccal pumping (or continuous flow as seen within these flow tank experiments). We hypothesize (Fig.…”
Section: Discussionmentioning
confidence: 99%